PENGARUH KOMPETENSI SDM, SISTEM INFORMASI AKUNTANSI, SISTEM PENGENDALIAN INTERN TERHADAP KUALITAS LAPORAN KEUANGAN DANA BANTUAN OPERASIONAL SEKOLAH (BOS) (Studi Kasus Sekolah Dasar Se-Kecamatan Kartasura) - Levia Handayani; Desy Nur Pratiwi; Indra Lila Kusuma (Jurnal Ilmiah Manajemen dan Akuntansi, 2025)
This study aims to examine the influence of human resource competence, accounting information systems, and internal control systems on the quality of school operational assistance (BOS) fund financial reports in elementary schools in Kartasura District. This study uses primary data obtained through interviews, questionnaires, and literature studies. The population in this study was 48 elementary schools in Kartasura District, the sampling technique used total sampling with a sample size of 48 elementary schools consisting of 96 respondents, namely the principal and school treasurer. The data analysis techniques used are descriptive statistics, instrument tests, classical assumption tests, and hypothesis tests. The results of this study show that human resource competence has a positive and significant effect on the quality of BOS fund financial reports with a significant value of 0.018 <0.05 and tcount 2.408> 1.987 ttable. The internal control system has a positive and significant effect on the quality of BOS fund financial reports with a significant value of 0.001 < 0.05 and tcount 3.491 > 1.978 ttable. While the accounting information system does not affect the quality of School Operational Assistance (BOS) fund financial reports with a significant value of 0.201 > 0.05 and tcount 1.289 < 1.987 ttable.